Dampak Faktor Makroekonomi terhadap Non Performing Loan pada Kredit Produktif Bank Umum di Indonesia - Alben Hernando; Elvaretta Miranda; Lauw Luvena Aileen Theodora; Yohanes B. Kadarusman; Glisera Agri Ariyan (Studi Akuntansi dan Keuangan Indonesia, 2020)
Non-performing loans are important for the banking industry, the existence of non-performing loans is a condition when the customers (debtors) are unable to pay their obligations. Based on the type of usage, researchers see an increase in non-performing of loans working capital and non-performing loans of investments which tend to increase because of that, this study aims to find out the factors that affect non-performing loans of productive loans of commercial banks registered in Otoritas Jasa Keuangan. This study is intended to be able to see the macroeconomic variables that affect productive credit NPLs. The sample used is a commercial bank in Indonesia which is registered in OJK. Productive credit NPL data are taken quarterly from 2003 to 2017 and 224 data are obtained in total. The regression model used in this study is ARDL with the help of processing Eviews 10 software. The macroeconomic variables to be tested in this research consist of GDP growth, loan interest rates growth, and IDR/ USD exchange rate growth. GDP growth and exchange rate growth have negative relationship, while loan interest rates growth doesn’t have significant relationship with dependent variable.